Evaluating the Effectiveness of Textbook Policy in Vietnam: A Grounded Research - Tâm, Nguyễn Thanh; Vinh, Lê Anh; Đức, Nguyễn Minh; Thắm, Phạm Thị Hồng; Hiền, Đặng Thị Minh; Diệp, Nguyễn Bích (Journal of Ecohumanism, 2025)
Vietnam’s school textbook policy has undergone a significant transformation alongside the implementation of the new 2018 general education curriculum, shifting from a single nationally unified set of textbooks to a "one curriculum - many textbooks" model. This groundbreaking policy reflects a positive change in the mindset of educational managers in Vietnam. However, the transition from a centralized, exclusive model to a decentralized approach in textbook publishing has presented various challenges. This study employs grounded theory to evaluate both the effectiveness and the challenges associated with Vietnam’s textbook policy. Data were collected through interviews conducted in four localities (Tuyen Quang, Hanoi, Quang Nam, Dong Nai) with participants from the general education system, including managers at all levels, teachers, parents, and students. The interviews continued until theoretical saturation was achieved. The effectiveness of the policy is demonstrated in several key areas: it has created a diversity of teaching and learning materials, improved the quality of education, reduced pressure on the state budget, and promoted a free market in text-book publishing.